TINGKAT KEBERHASILAN E-LEARNING SEBAGAI TEKNIK PJJ DALAM MEWUJUDKAN CAPAIAN PEMBELAJARAN SUDUT PANDANG DOSEN DAN MAHASISWA - Slamet Soesanto; Tatyana Tatyana; Ni Made Artini (ITB Swadharma, 2021)
The COVID 19 pandemic affects the socio-economic life of the community, including in the field of education, however the Teaching and Learning Process must continue. In order for the learning program to match the academic schedule and achieve learning outcomes, the use of educational technology (E-Learning) is a necessity. E-Learning, namely the use of electronic media to organize learning. This study aims to identify the effectiveness of E-Learning from the point of view of lecturers and students through three kinds of dimensions: 1. The Pedagogical Dimension identifies three aspects: a. E-Learning planning; b. Delivery of e-Learning; c. E-Learning interactivity. 2. Technology Dimensions consist of: a. Easy-to-use,economical e-Learning platform, b. internet network connectivity. 3. Dimensions of Quality Assurance: a. The effectiveness of the evaluation of the implementation of e-Learning; b. Inhibiting and supporting factors for the implementation of e-Learning, c. Quality standards for the implementation of e-Learning, d. Effectiveness in designing and making e-Learning learning materials. This research is an evaluation research with a discrepancy evaluation model. The determination of the sample was carried out using a purposive technique, considering that this research was conducted at the Faculty of Economics and Business ITBS Diploma 3 Program. The results of this study are expected to be useful as a lever for the improvement of Distance Learning programs in the future, specifically for ITBS Institutions, for lecturers, for students. The expected outputs: 1. The findings of inhibiting and supporting factors for the implementation of e-Learning, 2. The effectiveness of designing and making e-Learning learning materials. 3. The effectiveness of the e-Learning quality assurance methods and mechanisms. 4. Recommendations for the implementation of e-Learning from the aspects of the system, lecturers, students, infrastructure in the future.